Brussels versus the Beltway : advocacy in the United States and the European Union - Mahoney, Christine (American governance and public policy., 2008)
This book presents the first large-scale study of lobbying strategies and outcomes in the United States and the European Union, two of the most powerful political systems in the world. Every day, tens of thousands of lobbyists in Washington and Brussels are working to protect and promote their interests in the policymaking process. Policies emanating from these two spheres have global impactsthey set global standards, they influence global markets, and they determine global politics. Armed with extensive new data, Christine Mahoney challenges the conventional stereotypes that attribute any di.